Diabetes and Cancer: a Review of Current Knowledge - Wojciechowska, J.; Krajewski, W.; Bolanowski, M.; Kręcicki, T.; Zatoński, T. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Diabetes mellitus (DM), one of the most common life-threatening illnesses worldwide, is a group of metabolic diseases, characterized by sustained hyperglycemia. The global prevalence of diabetes mellitus among adults reached 387 millions in 2014 and is still rising. It is suggested there is a strong association between diabetes mellitus (especially type 2 diabetes mellitus) and carcinogenesis. The possible biological links between diabetes mellitus and cancer comprise hyperinsulinemia, hyperglycemia and fat-induced chronic inflammation. Although, the strongest association refers to pancreas and liver, there are many other organs involved in carcinogenesis in diabetic patients including breast, endometrium, bladder and kidney.Recent studies suggest that there is also association between cancer incidence and anti-diabetic medications. It was observed that some medications decrease the risk of carcinogenesis and some increase that risk. The majority of studies concern metformin, a drug of choice in type 2 diabetes mellitus, and its anti-neoplastic and tumor-suppressing activity. The positive effect of metformin was found in numerous researches investigating breast, pancreas, liver, colon, ovaries and prostate tumors.Because a variety of studies have suggested that diabetes mellitus and cancer are frequently coexisting diseases, recently published studies try to explain the influence of diabetes mellitus and anti-diabetic medications on carcinogenesis in different organs.We present the review of the latest studies investigating the association between both diabetes mellitus and anti-diabetic medications and cancer incidence and prognosis.Particularly we highlight the problem of concomitant head and neck cancers in diabetics, rarely analysed and often omitted in studies.
Keywords: antidiabetic medications; cancer; diabetes